Reflecting through the designing: a brief analysis of the teacher's planning process - Francesca Anello (Firenze University Press, 2016)
The aim of this work is to study the conditions in which teachers plan and execute educational actions in the classroom and to find out which difficulties they encountered during the development of the planned teaching action. The "concrete operations" that 15 teachers in the Palermo area had accomplished, were highlighted before, during and after every structured activity to promote the pupils' oral expression. Specifically, the research, which is collocated in the case study, had the function of verifying forty descriptors. These were grouped in the five cardinal points of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), with a motivated group of teachers that were formed during the action-research. To check intentions and behaviors of teachers, tools for self-analysis were built, individual notes and shared reports of the practice were used. The teachers found that the proposed projected device, initially, designed with 40 descriptors was not practical and chose only 20 of these. A simplified and flexible model is now available for the didactical preparation of the activities. Riflettere attraverso la progettazione: breve analisi del processo di programmazione didattica dell'insegnante L'obiettivo del contributo è indagare le condizioni in cui gli insegnanti pianificano e realizzano un intervento in classe, e quali difficoltà incontrano nelle fasi di sviluppo dell'azione didattica programmata. Sono state evidenziate le "operazioni concrete" che 15 insegnanti del territorio di Palermo hanno compiuto prima, durante e dopo un'attività strutturata per promuovere negli alunni l'espressione orale. Nello specifico la ricerca, che si colloca nella tipologia dello studio di caso, si è occupata di verificare la funzionalità di 40 descrittori, raggruppati nei cinque punti cardine del modello ADDIE (Analysis, Design, Development, Implementation, Evaluation), con un gruppo motivato di insegnanti che si erano formati durante una ricerca-azione. Per precisare intenzioni e comportamenti dei docenti sono stati costruiti strumenti di autoanalisi e ci si è avvalsi della scrittura individuale e del resoconto condiviso della pratica. Gli insegnanti hanno trovato poco funzionale il dispositivo progettuale con 40 descrittori inizialmente proposti e ne hanno scelti 20; ora è disponibile un modello semplificato e flessibile per la progettazione delle attività didattiche.